Electrochemical conversion of carbon dioxide over silver-based catalysts: Recent progress in cathode structure and interface engineering. (28th April 2021) - Nguyen, Dang Le Tri; Do, Ha Huu; Nguyen, Manh Tung; Vo, Dai-Viet N.; Nguyen, Van-Huy; Nguyen, Chinh Chien; Kim, Soo Young; Le, Quyet Van
Graphical abstract: Highlights: The electrochemical conversion of CO2 to value-added chemicals and fuels is emerging. We discuss the recent progress of CO2 electroreduction to CO over Ag-based catalysts. The existing challenges and prospects are presented. Abstract: Electrochemical CO2 reduction (ECR) to CO and other high-value chemicals is emerging as a prominent technology, which entails using the electricity produced from renewable energy resources to convert the problematic CO2 greenhouse gas into value-added chemicals and fuels. In addition to Au electrocatalysts, which are high-cost materials, Ag-based electrocatalysts have been regarded as promising ECR to CO alternatives in recent years, especially with their excellent activity and lowered cost of electrocatalyst synthesis because Ag is much more abundant and inexpensive. In this study, we firstly introduce some possible reaction mechanisms for Ag electrocatalysts in ECR to CO. To identify an outstanding strategy to develop a guideline for Ag-based electrocatalysts, we comprehensively reviewed recent advances in material development and interfacial engineering based on some critical factors and effects. Finally, a summary and prospects toward the future development of electrocatalysts for ECR are provided.